Robustness of hypofractionated breast radiotherapy after breast-conserving surgery with free breathing - Chen, Kunzhi; Sun, Wuji; Han, Tao; Yan, Lei; Sun, Minghui; Xia, Wenming; Wang, Libo; Shi, Yinghua; Ge, Chao; Yang, Xu; Li, Yu; Wang, Huidong (Frontiers in Oncology, 2023)
Purpose: This study aimed to evaluate the robustness with respect to the positional variations of five planning strategies in free-breathing breast hypofractionated radiotherapy (HFRT) for patients after breast-conserving surgery.Methods: Twenty patients receiving breast HFRT with 42.72 Gy in 16 fractions were retrospectively analyzed.Five treatment planning strategies were utilized for each patient, including: 1) intensity-modulated radiation therapy (IMRT) planning (IMRTpure); 2) IMRT planning with skin flash tool extending and filling the fluence outside the skin by 2 cm (IMRTflash); 3) IMRT planning with planning target volume (PTV) extended outside the skin by 2 cm in the computed tomography dataset (IMRTePTV); 4) hybrid planning, i.e., 2 Gy/fraction threedimensional conformal radiation therapy combined with 0.67 Gy/fraction IMRT (IMRThybrid); and 5) hybrid planning with skin flash (IMRThybrid-flash). All plans were normalized to 95% PTV receiving 100% of the prescription dose. Six additional plans were created with different isocenter shifts for each plan, which were 1, 2, 3, 5, 7, and 10 mm distally in the X (left-right) and Y (anterior-posterior) directions, namely (X,Y), to assess their robustness, and the corresponding doses were recalculated. Variation of dosimetric parameters with increasing isocenter shift was evaluated.Results: All plans were clinically acceptable. In terms of robustness to isocenter shifts, the five planning strategies followed the pattern IMRTePTV, IMRThybrid-flash, IMRTflash, IMRThybrid, and IMRTpure in descending order. V95% of IMRTePTV maintained at 99.6%±0.3% with a (5,5) shift, which further reduce to 98.2%±2.0% with a (10,10) shift. IMRThybrid-flash yielded the robustness second to IMRTePTV with less risk from dose hotspots, and the corresponding V95% maintained >95% up until (5,5).Considering the dosimetric distribution and robustness in breast radiotherapy, IMRTePTV performed best at maintaining high target coverage with increasing isocenter shift, while IMRThybrid-flash would be adequate with positional uncertainty < 5 mm.